PERKEMBANGAN KOGNITIF ANAK USIA DINI MELALUI PERMAINAN TEBAK GAMBAR - Fitri, Nur Annisa; Saudah, Saudah; Aghnaita, Aghnaita; Muzakki, Muzakki; Nurmiti, Nurmiti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2024)
Cognitive development is the development of the mind for understanding, reasoning, knowledge and understanding. Every day in their lives children experience mental development, such as learning to know people, getting to know things and learning new abilities. The aim of this research is to describe the cognitive development of children aged 5-6 years through the picture guessing game at Mekar Sari Kindergarten. This research uses a qualitative type of research. The research data sources include primary data sources, namely: class teachers, accompanying teachers, Mekar Sari Kindergarten children aged 5-6 years, class B 1. The secondary data sources are: the Principal of Mekar Sari Kindergarten and document data in the form of: RPPH, RPPM, assessment sheet on children's cognitive development in the picture guessing game, photos of activities during the picture guessing game. Furthermore, data collection techniques include: interviews, observation and documentation. The results of this research show that the picture guessing game to develop children's cognitive abilities at Mekar Sari Muara Tuhup Kindergarten is through the picture guessing game, children are able to introduce the letters ABCD, children are able to distinguish between the largest and smallest shapes, children's abilities and knowledge about the game guess the picture. And there are 5 children who are developing very well (BSB) and there are 3 children who are starting to develop (MB) 2 are not yet developing (BB) 3 are developing according to expectations (BSH) out of the 13 children.